Applications of Congruence to Divisibility Theory - Lemma, Mulatu; Allard, Dustin (IJRDO -JOURNAL OF MATHEMATICS, 2017)
The concept of congruence plays a big role in the theory of divisibility. In our study we master different properties of congruence and deeply investigate its applications to the divisibility theory. We will observe that the concept of congruence is such a power technique in dealing with the concept of divisibility. Fermat’s and Wilson’s Theorems will be studied and applied in the theory of divisibility. Several impressive results and applications will be discussed with different mathematical techniques applied.